OPTIMALISASI PERAN DAN FUNGSI TAS DALAM PENINGKATAN KOMPETENSI SOSIAL - Yoseptry, Ricky; Wisnurat, Yuyus; Mukti, Rita Asmara; Cantika, Winda (STKIP PGRI Situbondo, 2025)
This research aims to optimize the role and function of School Administrative Staff (TAS) in improving social competence through community service programs. TAS social competencies are important to support an inclusive and collaborative work environment, which ultimately supports educational success. The approach used is a community service method through the stages of planning, organizing, implementing and monitoring the program. At the planning stage, TAS needs were identified regarding social competence through surveys and focus group discussions. The organizing stage involves forming an implementation team, scheduling activities, and providing relevant resources. Implementation of the program consists of interpersonal communication training, simulation of social situations in the work environment, and intensive mentoring. The supervision stage includes continuous evaluation of the development of participants' social competence through direct observation, interviews and filling out questionnaires. Results showed a significant increase in TAS's ability to interact with teachers, students, and parents more effectively. In the discussion, it was explained that the success of this program was supported by a participatory approach, supportive leadership, and a systematic evaluation mechanism. This research recommends the development of similar programs on an ongoing basis to ensure TAS's role as the main supporter in creating a harmonious and excellent service-oriented educational environment.